Preparing ecuadorian students to study in the United States - Maridueña Muñoz, María Guadalupe (2023)
This is a conversation between a teacher about issues that a teacher has to confront, and the choices that has to be made (together with the reasons behind those choices) during the process of the designing a course. It was just found out that the teacher has secured a teaching internship, a onemonth intensive course for adults to be held in Quito, Ecuador, next January. The teacher has no idea at this point what it will involve, but it is urgent to revisit the world of EFL and adult teaching after six years of teaching ESL to adolescents. Actually, the teacher will not be straying too far from what it has been done these past six years at the Singapore American High School, as the teacher will keep teaching English for academic purposes (EAP).............